2017
DOI: 10.17509/ijal.v7i2.8137
|View full text |Cite
|
Sign up to set email alerts
|

Communicative Aspects of Multilingual Code Switching in Computer-Mediated Communication

Abstract: The quintessential role of language has been punctiliously studied relative to intercultural communication, cultural heritage, social development, education, identity construction and many more domains. One forum wherein language is investigated is the Computer-mediated Communication (CMC), which provides a fertile ground for linguistic and sociolinguistic analyses. The present study aims at investigating the preferred codes used in code switching (CS), functions of CS, and the motives of users for employing C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…Having had mastery of one specific language, the mother tongue, one tends to switch to another language to accommodate and facilitate conversation. Code switching serves as a communicative strategy by lowering the barriers created by language differences (Caparaz & Gustilo, 2017). Switching between languages frequently during conversation is a natural process in bilingual and multilingual contexts, as speakers have language control over their respective languages (Kelkoula & Djailed, 2018).…”
Section: Code Switching and Its Formsmentioning
confidence: 99%
“…Having had mastery of one specific language, the mother tongue, one tends to switch to another language to accommodate and facilitate conversation. Code switching serves as a communicative strategy by lowering the barriers created by language differences (Caparaz & Gustilo, 2017). Switching between languages frequently during conversation is a natural process in bilingual and multilingual contexts, as speakers have language control over their respective languages (Kelkoula & Djailed, 2018).…”
Section: Code Switching and Its Formsmentioning
confidence: 99%
“…The study of (Caparas et al 2017) investigates the communicative aspects of Multilingual Code-Switching in Filipino Netspeak. The findings in the study have shown that Code Switching is mainly used by Filipino college students and industry professionals when communicating using social media.…”
Section: Background Of the Studymentioning
confidence: 99%
“…In this study, the speakers switched code mostly because of their lexical need. In some studies (Caparas and Gustilo, 2017;Jdetawy, 2011;Tajudin,2013) this function of code-switching dominated the number of code-switches for the reason of meeting a real lexical need or compensating for lack of an equal translation. Filipinos are bilinguals who use English as a second language.…”
Section: Lexical Needmentioning
confidence: 99%